Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
simply take one of the equations and solve for y then plug that equation into the other to get x. Once you get your x value just plug it back into the y equation that you found earlier to get your y value.
If you need additional help just ask.
could you please guide me through that?
alright. Let's do this:
Take the x-2y=2. Move the x to the other side via subtraction to get -2y= 2-x
Now you need to get y by itself so divide each side by -2.
You will then get y = (2-x)/-2. Now that you have this you can take this y value and plug it back into the other equation.
Not the answer you are looking for? Search for more explanations.
So you will have 3x-4((2-x)/-2)=8. Now solve for x. I hope you can do this... After you find the value of x. You plug it back into your equation of y = (2-x)/-2 to get your y value.
how do i solve for x? sorry, im rally bad n math =P
That's fine. Now ignore what I put above here is a faster way. You have your 2 equations.... Take the x-2y=2 and instead of solving for y, solve for x instead (don't have to deal with fractions then). Add the 2y over to the right to get x = 2+2y. With this in mind, plug this into the other equation of 3x-4y=8 for x.
Thus you will get 3(2+2y)-4y=8. Distribute the 3 within the () to get 6+6y-4y=8. Combine your like terms by subtracting 6y-4y=2y and moving the 6 to the 8 by subtraction. When that is all said and done, you will end up with 6y=6. Simply dividing both sides by 6 to get your y value which is 1.
Now that you have you y=1 plug that back into you x equation you found earlier of x=2+2y. So you will get x=2+2(1) in otherwords 4.
So x=4 and y=1.
oh that makes so much sense now =P thank you SOO MUCH =}